Essex introduction - Thorn, Frank; Thorn, Caroline; Rumble, Alexander (The University of Hull)
The introduction discusses the county boundary; the Hundreds, their rubrication, order, and revised name-forms; the state of the manuscript for the county; related or 'satellite' texts; the Ely Enquiry ("Inquisitio Eliensis"); the editorial history of earlier versions of the notes, and the current state of the revision. Some material in this introduction derives from the original printed edition published by Phillimore (1983) and edited by Alexander Rumble.